Government Strategies in Incorporating Public Aspirations into Development Planning in Balikpapan City - Buana , Ierene Patra; Saipul, Saipul; Surya , Iman; Momoh, Zekeri (JED (Jurnal Etika Demokrasi), 2025)
The urgency of this research arises from persistent concerns that formal participatory mechanisms in local development planning often prioritize procedural compliance over the substantive integration of public aspirations, thereby limiting policy legitimacy and equity. This study aims to examine how public aspirations are incorporated into regional development planning in Balikpapan City through hybrid participatory strategies. A mixed-methods approach was employed, combining quantitative simulation using the Slovin formula to estimate representative participation patterns with qualitative thematic analysis based on the Miles and Huberman framework to interpret institutional processes and outcomes. The findings reveal that participation effectiveness cannot be assessed merely by attendance rates or the volume of proposals submitted, but rather by the extent to which community aspirations are substantively integrated into official planning documents. The results demonstrate that institutional capacity plays a decisive role, with better-resourced districts achieving higher integration rates, while socioeconomic disparities systematically disadvantage marginalized groups. In addition, infrastructure-related proposals dominate the thematic distribution of integrated aspirations, indicating a policy bias that may underrepresent social, educational, health, and environmental concerns. The study concludes that inclusive and sustainable development planning requires continuous institutional capacity building, transparent prioritization mechanisms, and equity-sensitive participatory frameworks. The novelty of this research lies in its integrative hybrid-participation framework that simultaneously captures procedural participation and substantive policy integration. This study contributes to the literature and policy practice by providing an empirically grounded model for evaluating participatory effectiveness beyond symbolic inclusion, offering actionable insights for local governments seeking to enhance democratic governance and equitable development planning.